Efficacy and safety of SilverNovaTM skin cream in post-aesthetic skin procedures - Poojary, Shital; Rao, Kshitija; Jadhav, Avinash; Purohit, Sanjay; Kondadi, Pooja; Mehta, Anirudh (International Journal of Research in Medical Sciences, 2023)
Background: The objective of this study was to evaluate the efficacy and safety of SilverNovaTM skin cream composed of SilverSol® (a patented colloidal nano silver technology from American Biotech Labs, USA) with other skin rejuvenators (coconut oil, vitamin E, and hyaluronic acid), in post-aesthetic skin procedure subjects. Methods: In this prospective, interventional, open-label, multicentric study, subjects who undergone post aesthetic procedures were enrolled to receive the application of SilverNovaTM skin cream twice daily. The subjects received the topical application for seven days, after which they were followed up for the next seven days. Endpoints were assessed at baseline and the end of the treatment (EOT). Primary endpoints were the investigator-assessed erythema, edema, dryness/scaling score, and the subject-assessed product tolerability in terms of burning, stinging, itching, and dryness/tightness. Results: A total of 60 subjects completed the study. There was a significant improvement in erythema, edema, and dryness/scaling score (p<0.0001). There was also significant improvement in burning, itching, and dryness/tightness scores. The physician global improvement assessment scale score was reduced from 3.3 to 1.38 (p<0.0001), showing the resolution of the symptom severity post-treatment with SilverNovaTM skin cream. Colorimetric characterization showed significant improvement in values at the end of the study, reflecting the improvement in skin color and erythema reduction. No adverse events were reported during the study. Conclusions: The application of SilverNovaTM cream in the immediate post procedure period significantly reduced the downtime of the treatment and improved patient acceptance of the treatment. This indicates that SilverNovaTM skin cream is a promising therapeutic option for managing the complications associated with aesthetic skin procedures without any safety concerns.